Оцінка залишкового ресурсу корпусів парових турбін АЕС - Черноусенко, Ольга Юріївна (НТУ "ХПІ", 2016)
Обґрунтовано продовження терміну експлуатації енергетичного обладнання шляхом розрахункових досліджень теплового, напружено-деформованого стану та оцінки залишкового ресурсу корпусу циліндра високого тиску парової турбіни К-1000-60/3000 блоку 1000 МВт "Рівненська АЕС" державне підприємство НАЕК "Енергоатом". Розрахунковий ресурс металу корпусу циліндра високого тиску турбоагрегату К-1000-60/3000 ст. № 3 Рівненської АЕС вироблений на 10 %. Запаси короткочасної статичної міцності корпусу циліндра високого тиску ніде не виходять за межі допустимих. Індивідуальний залишковий ресурс корпусу циліндра високого тиску парової турбіни К-1000-60/3000 становить 272676 годин, що дозволяє продовжити експлуатацію корпусу циліндра високого тиску на 10 років по умовах роботи реактору.

The experience of the operation of nuclear power plants allows us to substantiate the revision of earlier specified lifetime for the power units of nuclear power plants. In December 2016 the specified lifetime expires for the power unit No3 at the Rivne NPP equipped with the reactor of a BBEP-1000 type and the turbine К-1000-60/3000 and the residual life of the equipment must be evaluated to provide a reliable operation for new power units and the reduction of the expenditures for putting them into the operation. The purpose of this scientific paper is to extent the operation life for the power equipment. For structurally complicated HPC casings three-dimensional structures with horizontal flanges, steam supply pipe branches and other elements are taken into account. The methods were developed to create dimensional analogues of the elements of turbine machines using Solidworks software product for the HPC casing. The geometric model was constructed on the basis of the certificate drawing for the К-1000-60/3000 turbine.
Evaluation of the residual life of the casings of steam turbines used by nuclear power plants (NPP)
Keywords: тепловий стан; напружено-деформований стан; статична міцність; малоциклова втома; циліндр високого тиску; понад проектний період; thermal state; statistical strength; low-cycle fatigue; high pressure cylinder